Adaptive analysis of inelastic problems with Bodner-Partom constitutive model - Cecot, Witold (Computer Assisted Methods in Engineering and Science, 2022)
The Bodner- Partom elastic-visco-plastic constitutive equations [4] were used for numerical analysis of inelastic problems. This rate-dependent model makes it possible to describe elastic, plastic and viscous processes in metals, including temperature and continuum damage effects. The adaptive finite element method [9] was applied to approximate solution of the governing equations with two a posteriori error estimates that control accuracy of time and space discretization of displacements and internal variables. The paper addresses a further development of the methodology proposed by the author in previous works [7, 8] and used in [6]. We present here certain additional theoretical background and propose a novel strategy of adaptation as well as verify the method of solution transfer.